Pengaruh DER, EPS, ROE, ROA, CR dan Firm Size Terhadap Harga Saham Industri Barang Konsumsi - Wiranti, Windi; Kurniawan, Rudy; Astarani, Juanda (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze how financial ratios such as Debt to Equity Ratio, Earning Per Share, Return on Equity, Return on Asset, Current Ratio, and Firm Size affect Stock Prices. Industrial sector companies are the focus of this study, particularly consumer goods companies, with samples obtained using purposive sampling. From 28 consumer goods companies listed on the Indonesia Stock Exchange from 2020 to 2023, the researcher obtained 112 samples. This quantitative study used multiple regression analysis with the Eviews-12 program. The results showed that the Debt to Equity Ratio and Earning Per Share had a significant positive impact on stock value. Conversely, the results indicate that stock prices are negatively impacted by the financial ratios Return on Equity and Firm Size. Meanwhile, Return on Assets and Current Ratio have little influence on stock prices. The Adjusted R-Square value of 0.296 indicates that 29.6% of stock price variation is accounted for by the independent variables, with the remainder attributed to other factors outside the variables.
Keywords: Debt to Equity Ratio; Earning Per Share; Current Ratio; Firm Size; Stock Prices